2017
DOI: 10.1017/s136898001700283x
|View full text |Cite
|
Sign up to set email alerts
|

Where are the low-calorie sweeteners? An analysis of the presence and types of low-calorie sweeteners in packaged foods sold in Brazil from food labelling

Abstract: There was high prevalence of packaged foods with LCS, especially in food groups that form the basis of the Brazilian diet. The study was the first to extensively analyse the presence and types of LCS in packaged foods available for sale in a Brazilian supermarket and can be useful to monitor the use of LCS in these foods, as well as to support future changes in legislation to label sugars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
3
22
1
1
Order By: Relevance
“…Consequently, 51.9% of the food expenses are destined to buy processed foods that eventually might contain NCSs. On the other hand, we also compared our results with those from similar studies carried out in other countries (34)(35)(36)(37). Chile was clearly the country with the highest proportion of NCS-containing food products (55.5%), Brazil being the second with 24.4%, i.e., less than half what is reported in Chile.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Consequently, 51.9% of the food expenses are destined to buy processed foods that eventually might contain NCSs. On the other hand, we also compared our results with those from similar studies carried out in other countries (34)(35)(36)(37). Chile was clearly the country with the highest proportion of NCS-containing food products (55.5%), Brazil being the second with 24.4%, i.e., less than half what is reported in Chile.…”
Section: Discussionmentioning
confidence: 54%
“…Finally, Table 3 summarized the results from similar studies carried out in other countries from Latin America [Brazil (34), Mexico (35)], North America [USA (36)], Europe [Spain (37)], and Oceania [New Zealand and Australia (35)]. Chile shows a much higher proportion of NCS-containing foodstuffs, globally as well as in each considered food group.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The IBGE food/beverage categories identified as containing LNCS in the current studies overlap the categories identified in a recent study by Figueiredo et al (2018) that summarised information on the presence of LNCS in packaged foods and beverages sold in a supermarket in Brazil. Most of the food/ beverage categories with the highest prevalence of LNCS usage in the Figueiredo et al (2018) studyi.e., baked goods (including cakes and granola bars), dessert mixes, powdered drinks, soft drinks, jelly, and candy -were also identified in the current study as containing LNCS, thus lending support to the use of the IBGE survey data to assess intake of LNCS by the Brazilian population.…”
Section: Discussionmentioning
confidence: 63%
“…To the best of our knowledge, our survey is the fifth in Brazil investigating all food product labels in a single supermarket; the other studies were conducted in the same supermarket chain as that of the present study ( 24 27 , 43 49 ) .…”
Section: Discussionmentioning
confidence: 99%